2016
DOI: 10.1016/j.cmi.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Molecular quantification of bacteria from respiratory samples in patients with suspected ventilator-associated pneumonia

Abstract: Ventilator-associated pneumonia (VAP) is the most common infection in critically ill patients. Initial antibiotic therapy is often broad spectrum, which promotes antibiotic resistance so new techniques are under investigation to obtain early microbiological identification and quantification. This trial compares the performance of a new real-time quantitative molecular-based method with conventional culture in patients with suspected VAP. Patients with suspected VAP who were ventilated for at least 48 h were el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 15 publications
(14 reference statements)
0
31
0
Order By: Relevance
“…Experience with BAL PCR in LTx recipients is limited to P. jirovecii and respiratory viruses, the foremost being cytomegalovirus . Unlike the clinical scenario studied herein, a multitude of studies assessing multiplex PCR in patients with suspected ventilator‐associated pneumonia argue for its usefulness in the ICU setting . None of the patients in this study, however, was transferred to the ICU, where a time difference of 2 hours might bear greater significance.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Experience with BAL PCR in LTx recipients is limited to P. jirovecii and respiratory viruses, the foremost being cytomegalovirus . Unlike the clinical scenario studied herein, a multitude of studies assessing multiplex PCR in patients with suspected ventilator‐associated pneumonia argue for its usefulness in the ICU setting . None of the patients in this study, however, was transferred to the ICU, where a time difference of 2 hours might bear greater significance.…”
Section: Discussionmentioning
confidence: 95%
“…9,10 Unlike the clinical scenario studied herein, a multitude of studies assessing multiplex PCR in patients with suspected ventilator-associated pneumonia argue for its usefulness in the ICU setting. [11][12][13][14]…”
Section: Time To Final Diagnosismentioning
confidence: 99%
“…This is an FDA approved and CE marked platform that uses nested real-time PCR to detect 34 clinically important respiratory targets (15 semi-quantitative bacterial targets, 3 qualitative atypical bacterial targets, 8 resistance genes and 8 viral targets [30][31][32] Furthermore, the pneumonia panel detects pathogens in a much higher proportion of samples than culture. Buchan et al 31 reported that the Filmarray detected a bacterial target in 71% more specimens than routine culture, equating to over 100% increase in total bacterial detections.…”
Section: Biofire Filmarray Pneumonia Panel 29mentioning
confidence: 99%
“…Verigene is a nanoparticle-based amplification method for identifying Gram-negative species and resistance genes, but this panel is currently FDA-approved only for positive blood cultures [22]. Ribosomal amplification (e.g., 16S ribosomal RNA gene PCR) has also been evaluated in suspected VAP cases [23, 24]. …”
Section: Vap Epidemiology: Definitions Surveillance and Diagnostic mentioning
confidence: 99%